Adaptive assessment of the capacity of cognitive control. Issue 1 (January 2022) - He, Xu; Qiu, Boyu; Deng, Yingyu; Liu, Ting; Chen, Yanrong; Zhang, Wei
Cognitive control, although it has limited capacity, serves an essential role in supporting a broad range of cognitive functions. The backward masking majority function task (MFT-M) is a validated behavioural method for measuring the capacity of cognitive control (CCC), but the administration is lengthy. We tested the relative efficiency of administering the MFT-M using an adaptive method based on the principles of computerised adaptive testing (CAT). Participants were 40 healthy young adults aged 18–26. Scores on the adaptive version were highly correlated with scores based on the original approach to administration and showed high test–retest reliability. In addition, compared with the original task of 864 trials (about 86 min), less than 216 trials (20 min) were required in the adaptive version. The results suggest that CAT is a valid and more efficient method for assessing CCC than the MFT-M. This study provides an example of adaptive trial selection in task administration, an approach that can advance the methodology of behavioural science.